Exploring the Role of Epicardial Adipose Tissue in Coronary Artery Disease From the Difference of Gene Expression - Wang, Qian-Chen; Wang, Zhen-Yu; Xu, Qian; Li, Ruo-Bing; Zhang, Guo-Gang; Shi, Rui-Zheng (Frontiers in Physiology, 2021)
Objectives: Epicardial adipose tissue (EAT) is closely adjacent to the coronary arteries and myocardium, its role as an endocrine organ to affect the pathophysiological processes of the coronary arteries and myocardium has been increasingly recognized. However, the specific gene expression profiles of EAT in coronary artery disease (CAD) has not been well characterized. Our aim was to investigate the role of EAT in CAD at the gene level. Methods: Here, we compared the histological and gene expression difference of EAT between CAD and non-CAD. We investigated the gene expression profiles in EAT of patients with CAD through high-throughput RNA sequencing (RNA-Seq), we performed bioinformatics analysis such as functional enrichment analysis and protein-protein interaction (PPI) network construction to obtain and verify the hub differentially expressed genes (DEGs) in EAT of CAD. Results: Our results showed that the size of epicardial adipocytes in CAD group was larger than the control group. Our findings on the EAT gene expression profiles of CAD showed a total of 747 DEGs (fold change >2, p value <0.05). The enrichment analysis of DEGs showed that more pro-inflammatory and immunological genes and pathways were involved in CAD. Ten hub DEGs (GNG3, MCHR1, BDKRB1, MCHR2, CXCL8, CXCR5, CCR8, CCL4L1, TAS2R10 and TAS2R41) were identified. Conclusion: EAT in CAD shows unique gene expression profiles and may act as key regulators in CAD pathological process.